The good and the bad of preprint servers in plant physiology - Kronzucker, Herbert J.; Qiu, Quan Sheng; Sonnewald, Uwe (Journal of Plant Physiology, 2022)
Preprint servers allow rapid publication of research findings by eliminating the time gap between submission and publication associated with editorial and peer review of scientific works. Consequently, non-peer-reviewed articles are essentially accessible immediately to researchers and the public. There are many valid justifications for sharing work on preprint servers, such as the ability to collect feedback from the research community and improve work prior to journal submission and a reduced risk of work being “scooped” by competitors. Rapid access to the latest scientific developments can furthermore expedite progress in important research areas. Significant downsides of preprint servers, however, are that the public, including members of the media and policy makers, cannot judge the quality of such non-reviewed publications and that misinformation may be spread. Balancing the good and the bad of preprint servers as opposed to classic peer review, we provide guidance for authors of the Journal of Plant Physiology.
CRIS-Team Scopus Importer:2022-04-01